Evaluasi Kebijakan Tanggung Jawab Sosial Lingkungan Perusahaan Di Pt. Sirtu Karya Utama Kelurahan Buluri Kecamatan Ulujadi Kota Palu - Syaputra, Agung; Kurnia, Intam; Tawil, Yulizar Pramudika (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The researcher chose to study the Corporate Social Responsibility (CSR) policy of PT. Sirtu Karya Utama due to the inconsistency between the implemented programs and the applicable regulations. This research aims to evaluate the Company's Environmental Social Responsibility Policy at PT. Sirtu Karya Utama in Buluri Village, Ulujadi District, Palu City. The research method used in this study is a qualitative method with a descriptive approach. The informants in this study numbered 6 people. Data collection techniques used interviews, observations, and documentation. Data analysis involved data collection, data reduction, data presentation, and conclusion drawing. The theory used from William N. Dunn (2003: 429-438) consists of 6 indicators: Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Appropriateness. Based on the research results, it shows that the Company's Environmental Social Responsibility Policy at PT. Sirtu Karya Utama in Buluri Village, Ulujadi District, Palu City, has not been implemented well. This can be seen in terms of Effectiveness, namely the company's non-compliance with government-established regulations, in the Efficiency indicator, its implementation in the field, which results in the less effective and efficient achievement of the objectives of the regional regulation, which is for the welfare of the community and sustainable development, in the Adequacy indicator, due to the lack of evaluation and revision of the policy, which will hinder the occurrence of continuous improvement in the company's practices in the field, in the Equity indicator, caused by the government's indifference in encouraging company participation and protecting the interests of the community around the mine, in the Responsiveness indicator, PT. Sirtu Karya Utama, together with the city government, is considered less responsive to community complaints regarding the negative impacts of mining activities, and in the Appropriateness indicator, there is an inconsistency between the established policy and practices in the field.